A Systematic Review of Factors Influencing Nurses Clinical Risk Identification Skills: Implications for Patients Safety - Chandra, Eka Yufi Septriana; Wijaya, Dodi; Asmaningrum, Nurfika (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Patient safety is considered an important part of healthcare and also plays an important role in preventing and reducing harm, errors, and injuries that can occur during the care cycle. One way to address this challenge is to develop systematic clinical risk management. This study aims to determine the ability of nurses to identify clinical risks through risk management. The research used was a systematic review using the PRISMA protocol in selecting articles. The results showed 10 articles were identified and published in 2014-2024. All articles studied were indexed by Scopus. The study found two main factors that can affect nurses' ability to identify clinical risks, namely intrinsic and extrinsic factors. The largest factor was found in extrinsic factors which found that effective communication is the main factor that can affect nurses' ability to identify clinical risks in patients in hospitals. Keywords: Nurses, Nursing abilities, Identification Skills, Clinical Risk, Patient Safety